Inteligencia interpersonal y logros de aprendizaje en estudiantes de segundo grado de secundaria del área de ciencias sociales I.E.M. Colegio Nacional Iquitos 2021 - Perez Rengifo, Jorge Luis (2022)
The objective of the study was: To analyze the relationship that exists between interpersonal intelligence and learning achievements in the area of Social Sciences in second-grade students of the Iquitos National College Mixed Educational Institution Secondary, during the year 2021. The study was descriptive and correlational. The general design used in the research was non-experimental cross-correlational research. The study was developed with a population and sample of 120 second-grade high school students from the Iquitos National College Mixed Educational Institution Secondary. When analyzing the relationship between interpersonal intelligence and learning achievements in second year high school students of Social Sciences of the I.E.M. Colegio Nacional Iquitos, applying t-student statistical tables, locating with 2 degrees of freedom and an alpha (?) value of 0.05; concluding that there is a highly significant relationship between interpersonal intelligence and learning achievements in the area of Social Sciences in second grade students of Secondary I.E.M Iquitos National School during the year 2021.